GOVERNANCE OF HEALTHCARE SYSTEM: FRAMEWORKS FOR GENDER MAINSTREAMING INTO PUBLIC HEALTH - Rehman, Adeela (LIFE: International Journal of Health and Life-Sciences, 2017)
The governance of health system is a very important aspect to consider ensuring the equitable distribution of healthcare services to the population. The governance of health system is based on the equitable provision of resources, designing of appropriate strategies to improve the health conditions and people well-being, by adhering to proper, adequate rules and procedural guidelines for measuring its actions. This paper presents the gender-based governance frameworks designed by several health organizations to measure the performance of a health system. These governance frameworks were adopted from the annual reports of International health organizations and analyzed through the perspective of gender. There is a need to measure the governance of a health system within the particular framework. In this light, to regulate the structure of governance, the government is responsible to assure the provision of health services both in the public and private sectors. Unfortunately, the process of planning and financing health care services lacks accountability. Thus, to ensure a gender balanced structure of governance in the health system, there is a need to integrate the gender perspective on all levels of health system starting from the policy to its implementation.